Soft skills gap: aligning higher education with job market needs in Spain - Ojan, Marina-Paola; Lara-Navarra, Pablo; Sánchez-Navarro, Jordi; Clares-Gavilán, Judith (International Journal of Evaluation and Research in Education (IJERE), 2025)
In the dynamic and complex context surrounding the fourth and fifth industrial revolution, dominated by volatility and uncertainty, the importance of communication training, particularly in developing soft skills, is evident. This study advocates for the inclusion of these competencies in higher education and professional training in communication, ensuring they align with the current needs of the Spanish labor market. The gap between the competencies taught and those required by employers is examined to strengthen the connection between academic training at university level and work adaptability. The research examines the gap between the skills taught and those required by employers, aiming to strengthen the connection between university education and workplace adaptability. It emphasizes the need for greater alignment between academic profiles and job demands, proposing comprehensive search and analysis methods for improvement. Additionally, the study underscores the significance of communication training in preparing students for both present and future challenges. Adaptability and continuous updating of soft skills are essential for maintaining professional competitiveness in today’s era.